Critical Review: The Negative Impacts of Social Media-Induced Fear of Missing Out (FoMO): Online Stalking, Social Comparison, and Digital Fatigue - Akbar Nur Aziz; Azam Syukur Rahmatullah (G-Couns: Jurnal Bimbingan dan Konseling, 2025)
The purpose of this article is to analyze in depth the criticism of the negative impact of social media addiction which gives rise to FoMO attitudes. This research uses a critical observation method with a qualitative descriptive approach, with a focus on in-depth analysis of the methodology, conclusions and discussion of the main article. The main reference comes from the article entitled "Dark Consequences of Social Media-Inducing Fear of Missing Out (FoMO): Social Media Stalking, Comparisons, and Fatigue" written by Tandon et al., and published in October 2021. The article reviews in detail critical methodology, findings, and discussion. The results of the analysis show a complex interaction between Fear of Missing Out (FoMO), social comparison, social media stalking, and digital fatigue, which has a significant impact on adolescents' psychological well-being. This critical review provides new insights into the psychological mechanisms behind excessive social media use and its impact on the mental health of young people. This research highlights the need for educational and awareness interventions to reduce the negative impact of social media use on adolescents. Keywords: dark side of social media, fear of missing out (FoMO), online social comparison, social media fatigue, social media stalking